Leaping and vortex motion of the shock aurora toward the late evening sector observed on 26 February 2023 - S. Nanjo; M. Yamauchi; M. G. Johnsen; Y. Yokoyama; U. Brändström; Y. Ogawa; A. N. Willer; K. Hosokawa (Annales Geophysicae)
On 26 February 2023, a shock aurora triggered by an interplanetary (IP) shock was observed in northern Scandinavia at 21 MLT (magnetic local time). Previously, ground-based observations of shock auroras have primarily been conducted on the dayside, where IP shocks hit. However, this study successfully observed the shock aurora on the nightside at 21 MLT. This is the first time the morphology of a shock aurora has been observed on the nightside using ground-based cameras. We introduce the observational results by four ground-based cameras and a magnetometer network in the Northern Hemisphere. Previous observations have shown that shock auroras consist of two types of optical signatures, i.e., diffuse and discrete auroras, with a few minutes of separation. In this study, three distinct signatures were observed with a few minutes of lag: (1) a luminosity enhancement of an arc-shaped green aurora, (2) the appearance of red auroras, and (3) leaping of discrete auroras toward the nightside (anti-sunward) with a vortex-like structure. While red emissions have been previously observed in shock auroras, this is the first time undulating and jumping structures have been discovered. Comparison with equivalent currents estimated from the magnetometer network showed that the first luminosity enhancement occurred within 1 min after the onset of the geomagnetic variation induced by the IP shock, the so-called geomagnetic sudden commencement (SC), and the red aurora observed after the formation of upward field-aligned currents over northern Scandinavia. Furthermore, the propagation speed of the aurora in (3) was on the same order as the solar wind speed in interplanetary space, as reported in previous studies. These newly identified morphological features of the shock aurora provide a valuable insight into how current systems associated with SC propagate toward the nightside.